Can common dietary assessment methods be better designed to capture the nutritional contribution of neglected, forest, and wild foods to diets? ... : هل يمكن تصميم طرق التقييم الغذائي الشائعة بشكل أفضل لالتقاط المساهمة الغذائية للأطعمة المهملة والغابات والبرية في الوجبات الغذائية ؟ ... - J. Raneri; Julia Boedecker; Diego A. Fallas Conejo; Giulia Muir; Giles Hanley‐Cook; Carl Lachat (OpenAlex, 2023)
Food systems are the primary cause of biodiversity loss globally. Biodiversity and specifically, the role that wild, forest and neglected and underutilised species (NUS) foods might play in diet quality is gaining increased attention. The narrow focus on producing affordable staples for dietary energy has contributed to largely homogenous and unhealthy diets. To date, evidence to quantify the nutritional contribution of these biodiverse foods is limited. A scoping review was conducted to document the methods used to quantify the contribution of wild, forest and NUS foods. We found 37 relevant articles from 22 different countries, mainly from Africa (45%), the Americas (19%), and Asia (10%). There were 114 different classifications used for the foods, 73% of these were specifically related to wild or forest foods. Most dietary assessments were completed using a single day qualitative or quantitative 24 h open recall (n = 23), or a food frequency questionnaire (n = 12). There were 18 different diet related ... : النظم الغذائية هي السبب الرئيسي لفقدان التنوع البيولوجي على مستوى العالم. يكتسب التنوع البيولوجي، وعلى وجه التحديد، الدور الذي قد تلعبه الأطعمة البرية والغابات والأنواع المهملة وغير المستغلة (NUS) في جودة النظام الغذائي اهتمامًا متزايدًا. ساهم التركيز الضيق على إنتاج المواد الغذائية الأساسية بأسعار معقولة للطاقة الغذائية في اتباع أنظمة غذائية متجانسة وغير صحية إلى حد كبير. حتى الآن، لا تزال الأدلة على تحديد المساهمة الغذائية لهذه الأطعمة المتنوعة بيولوجيًا محدودة. تم إجراء مراجعة استطلاعية لتوثيق الأساليب المستخدمة لتحديد مساهمة الأغذية البرية والغابات وأغذية جامعة سنغافورة الوطنية. وجدنا 37 مقالة ذات صلة من 22 دولة مختلفة، معظمها من أفريقيا (45 ٪) والأمريكتين (19 ٪) وآسيا (10 ٪). كان هناك 114 تصنيفًا مختلفًا للأغذية، 73 ٪ منها كانت مرتبطة على وجه التحديد بالأغذية البرية أو الحرجية. تم الانتهاء من معظم التقييمات الغذائية باستخدام استدعاء مفتوح نوعي أو كمي لمدة 24 ساعة في اليوم (العدد = 23)، أو استبيان تكرار الطعام (العدد = 12). تم استخدام 18 مؤشرًا مختلفًا متعلقًا بالنظام الغذائي، أهمها كفاية المغذيات (العدد ...